العقود الإلكترونية: دراسة فقهية تحليلية Electronic Contracts: A Jurisprudential Analysis - (Arif Ali Arif), عارف علي عارف; (& Nadia Al bayani), ونادية ياس البياتي (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
كان التطور في مجال تكنولوجيا المعلومات وقطاع الاتصالات الذي يمر به العالم في الوقت الراهن، أثره البالغ والواضح على المبادئ الراسخة في الفكر القانوني، خاصة في مجال العقد الإلكتروني، فبينما كانت هذه التصرفات تنشأ بواسطة العقد التقليدي، فإنه اليوم أصبح ينشأ بواسطة تقنيات رقمية. ثم إِن استخدام هذه التقنية الحديثة في إبرام التصرفات القانونية أحدث تغييرات في الكثير من المفاهيم القانونية كمفهوم العقد، إذ أوجدت هذه التقنيات أشكالاً جديدة صبغت جميعها بالطابع الإلكتروني، والتي تتصف بصفات وخصائص قد لا تتوافر في نظيرتها بالتجارة التقليدية، كالسرعة وتوفير المال والوقت والجهد، ولذلك تضافرت الجهود الدولية والإقليمية والوطنية على إصدار تشريعات تعترف بحجية هذه الأشكال الحديثة بذات الحجية المقررة للعقد التقليدي. ومع كل هذا التطور في شكل العقد، فإن الفقه الإسلامي لا يمنع الاستفادة من الأَساليب الفنية والتقنيات الحديثة خاصة في مجال العقود ووسيلة إبرامها طالما لا يتعارض مع الشريعة الإسلامية الغراء ويحقق العدالة والاستقرار وإثبات الحقوق بين الأَطراف. ******************* The development the world is experiencing at the moment in the field of information technology and telecommunications sector has a comprehensive and clear impact on the established principles in legal thought, especially in the field of electronic contracts. Transactions were in the past based on traditional contracts, whereas they take shape today by digital technologies. The use of this modern technology in concluding the legal procedures has effected many changes in many legal concepts such as the concept of the contract. The electronically fashioned new forms of contract are characterized by the features and properties that are not available in the forms used in the traditional trade such as swiftness and abundance of wealth, time, and effort. Therefore, united efforts at the international, regional and national level were made to pass legislations to recognize these modern forms as valid as those in traditional contracts. With all this development in the form of the contract, the Islamic jurisprudence does not preclude benefiting from the modern techniques and technologies, particularly in the area of contracts and the means by which they are concluded as long as it does not conflict with Islamic SharÊ‘ah, ensures justice, stability, and honors human rights of the parties.